Terminalia arjuna: A novel natural preservative for improved lipid oxidative stability and storage quality of muscle foods - Insha Kousar Kalem; Z.F. Bhat; Sunil Kumar; Ajay Desai (Food Science and Human Wellness)
The study was conducted to explore the possibility of utilization of Terminalia arjuna as a novel natural preservative in meat products by using chevon sausages as a model system. Chevon sausages were prepared by incorporating different levels of T. arjuna viz. T1 (0.25%), T2 (0.50%) and T3 (0.75%) and were assessed for various lipid oxidative stability and storage quality parameters under refrigerated (4 ± 1 °C) conditions. T. arjuna showed a significant (p < 0.05) effect on the lipid oxidative stability as the treated products exhibited significantly (p < 0.05) lower TBARS (mg malonaldehyde/kg) values in comparison to control. A significant (p < 0.05) effect was also observed on the microbial stability as T. arjuna incorporated products showed significantly (p < 0.05) lower values for total plate count (log cfu/g), psychrophilic count (log cfu/g), yeast and mould count (log cfu/g) and FFA (% oleic acid) values. Significantly (p < 0.05) higher scores were observed for various sensory parameters of the products incorporated with T. arjuna during refrigerated storage. T. arjuna successfully improved the lipid oxidative stability and storage quality of the model meat product and may be commercially exploited as a novel preservative in muscle foods. Keywords: Terminalia arjuna, Chevon sausages, Natural preservative, Lipid oxidation, Storage quality